Pengaruh Latihan Kelincahan Terhadap Kemampuan Tendangan Sabit Siswa Ekstrakurikuler di SMP PGRI 2 Palembang - Muhammad Ridwan; Siti Ayu Risma Putri; Putri Cicilia Kristina (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The problem with this research is that extracurricular students at SMP PGRI 2 Palembang still lack agility, this can be seen when sparring with fellow students because attacks are easily caught and read by opponents. Especially during the sickle kick. The aim of this research was to see the effect of agility training on sickle kicking ability. This research is a quasi-experiment, by providing agility training treatment to improve students' sickle kicking abilities, with a population of 20 students, a purposive sampling technique, with samples taken from 20 male students. The instrument in this research was a sickle kick ability test. Next, data analysis uses the t test to determine the effect. The research results showed 25.25 > 1.73, which means that there is an influence between agility training on the crescent kick ability of extracurricular students at PGRI 2 Middle School Palembang.